Mobility and the Hotel in Modern Literature - Short, Emma. author. aut Link
IX, 223 p. 1 illus.
Keywords: This book considers the complex ways in which the hotel functions to express the shifting experiences of modernity in the works of such authors as Anthony Trollope, Wilkie Collins, Arnold Bennett, H.G. Wells and Elizabeth Bowen. The text contributes to the critical debates on nineteenth- and twentieth-century literature concerning space, movement and mobility, arguing that the hotel reconfigures boundaries of modernist, middlebrow and popular fiction. Drawing on a range of interdisciplinary theoretical and analytical perspectives, the book provides a critical and cultural history of the hotel in British literature, charting its changing nature and usage from the mid-nineteenth century up until the interwar period.